Palavras Úmidas - Assis Carvalho, Edgard (Revista Cronos, 2016)
ALMEIDA, Maria da Conceição de. Palavras úmidas. Homenagens, prefácios e outros escritos. Josineide Silveira de Oliveira, Louize Gabriela Silva de Souza (Orgs.). Natal: EDUFRN, 2014. Coleção Baobá, v. 1. (426 páginas).